Correct Species Identification and Its Implications for Conservation Using Haploniscidae (Crustacea, Isopoda) in Icelandic Waters as a Proxy - Kürzel, Karlotta; Kaiser, Stefanie; Lörz, Anne-Nina; Rossel, Sven; Paulus, Eva; Peters, Janna; Schwentner, Martin; Martinez Arbizu, Pedro; Coleman, Charles Oliver; Svavarsson, Jörundur; Brix, Saskia (Frontiers in Marine Science, 2022)
Correct identification of species is required to assess and understand the biodiversity of an ecosystem. In the deep sea, however, this is only possible to a limited extent, as a large part of the fauna is undescribed and the identification keys for most taxa are inadequate or missing. With the progressive impact of climate change and anthropogenic activities on deep-sea ecosystems, it is imperative to define reliable methods for robust species identification. In this study, different techniques for the identification of deep-sea species are tested, including a combination of morphological, molecular (DNA barcoding, and proteomic fingerprinting), biogeographical and ecological modeling approaches. These are applied to a family of isopods, the Haploniscidae, from deep waters around Iceland. The construction of interactive identification keys based on the DELTA format (DEscription Language for TAxonomy) were a major pillar of this study, the evaluation of which was underpinned by the application of the supplementary methods. Overall, interactive keys have been very reliable in identifying species within the Haploniscidae. Especially in a deep-sea context, these types of keys could become established because they are easy to adapt and flexible enough to accommodate newly described species. Remarkably, in this study, the interactive key enabled identification of a supposedly new species within the Haploniscidae that was later verified using both molecular genetic – and proteomic methods. However, these keys are limited given that they are based on purely morphological characteristics, including where species with strong ontogenetic or sexual dimorphism occur as both genders are not always described. In this case, integrative taxonomy is the method of choice and the combination presented here has been shown to be very promising for correct identification of deep-sea isopods.